Profissão docente: uma rede de histórias - Isabel Lelis (Associacao Nacional de Pós-Graduação e Pesquisa em Educação, 2001)
This article proposes to analyse the social identity of teachers in the first series of primary education, forged through processes of professional, school and family socialization. Using the life stories of thirteen women teachers, the article discusses the significance attributed to theteaching profession. Taking Pierre Bourdieu´s sociology as reference, the study explores the constitution of the habitus in teachers, the strategies they use to achieve academic qualifications, admission to the profession and the weight of initialand continued training in the way teachers experience and represent their work. This study challenges the images of passivity, negligence and technical incompetence that are attributed to teachers by educational authorities and governamental agencies, by recognizing that, at a time in which a massification of school isoccuring, the social representation of teaching has been modified.